The Legislative Development of Investment and the Reasons for its Instability - Soltane, Amar (Journal of Human Sciences, 2022)
Since independence, the Algerian state has issued many laws related to investment that have produced contradictious methods to deal with the problem of private investment, and this is reflected in the situation of national development. Economic and technological growth rates are still modest in light of the fact that public treasury resources are largely linked to oil revenues, which implies major reforms. This research aims to introduce the various investment-related legislations, explain the economic implications thereof, deal with the problem of legal instability in this field, and to present appropriate proposals.